2023
DOI: 10.3389/fmicb.2023.1120285
|View full text |Cite
|
Sign up to set email alerts
|

Enteroaggregative Escherichia coli as etiological agent of endemic diarrhea in Spain: A prospective multicenter prevalence study with molecular characterization of isolates

Abstract: BackgroundEnteroaggregative Escherichia coli (EAEC) is increasingly associated with domestically acquired diarrheal episodes in high-income countries, particularly among children. However, its specific role in endemic diarrhea in this setting remains under-recognized and information on molecular characteristics of such EAEC strains is limited. We aimed to investigate the occurrence of EAEC in patients with non-travel related diarrhea in Spain and molecularly characterize EAEC strains associated with illness ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 75 publications
(130 reference statements)
0
2
0
4
Order By: Relevance
“…Это деление основано на наличии или отсутствии гена aggR, который кодирует активатор транскрипции экспрессии как хромосомных, так и плазмидо-кодируемых факторов вирулентности, включая AAF и дисперзин [39,46]. Высказано предположение, что t-EAgEC имеют больший патогенный потенциал [40,48]. Ряд исследователей указывают на возникновение вспышек диареи, вызванных a-EAgEC [6,14].…”
Section: энтероагрегативные E Coliunclassified
See 2 more Smart Citations
“…Это деление основано на наличии или отсутствии гена aggR, который кодирует активатор транскрипции экспрессии как хромосомных, так и плазмидо-кодируемых факторов вирулентности, включая AAF и дисперзин [39,46]. Высказано предположение, что t-EAgEC имеют больший патогенный потенциал [40,48]. Ряд исследователей указывают на возникновение вспышек диареи, вызванных a-EAgEC [6,14].…”
Section: энтероагрегативные E Coliunclassified
“…Несмотря на то что такие белковые компоненты, как дисперзин, Pic, ShET1, EAST-1 и Pet, участвуют в вирулентности EAgEC, ни один из них не присутствует во всех штаммах, поэтому предложено использовать triplex-ПЦР для выявле-ния 3 генов (aggR, aatA и aaiA), которая упрощает и унифицирует детекцию EAgEC, включая t-EAgEC и a-EAgEC [14]. В исследовании ряда авторов показано, что комбинация генов вирулентности может зависеть от географического региона [40,48], в связи с этим международный микробиологический надзор за EAgEC может улучшить надлежащий диагностический алгоритм [39].…”
Section: энтероагрегативные E Coliunclassified
See 1 more Smart Citation
“…Enteroaggregative Escherichia coli (EAEC) is associated with acute and chronic diarrhea worldwide as well as travelers' diarrhea. [1][2][3][4][5][6][7][8][9][10] Populations strongly affected by EAEC include children in developing countries and deployed military personnel. 1,9,11,12 Globally, diarrhea is the second leading cause of death in children under five.…”
Section: Introductionmentioning
confidence: 99%
“…25 SepA is a SPATE that is found in 21-60% of EAEC, depending on the study. 5,[26][27][28][29][30] Epidemiological data indicate that SepA may be important for disease caused by EAEC. For example, data from Mali collected during the MAL-ED study showed that sepA was the EAEC gene most strongly associated with diarrheal cases among children under five years of age.…”
Section: Introductionmentioning
confidence: 99%